The influence of health education with peer education and interactive diaskusi on knowledge of pregnancy problems is not desirable - Dwi Juwartini; Djauhar Ismail; Ova Emilia (Berita Kedokteran Masyarakat (BKM), 2016)
Effects of peer education and interactive group discussion on cognitive ability in dealing with unwanted pregnancy PurposeThis study aimed to determine the effectiveness of peer education methods and interactive discussions through audiovisual media on cognitive ability change in solving the problem of unwanted pregnancy.MethodsThis quasi-experimental study used a randomized control trial design involving 99 students. The instrument used was a questionnaire, with the module method of peer education and interactive discussions through audiovisual media, agency and facilitator.ResultsAdolescent reproductive health education after considering living with family consistently had a significant effect on increasing the average value of cognitive ability to solve the problem of unwanted pregnancy. Living with family can predict the cognitive ability of teenagers in solving the problem of unwanted pregnancy by 15%.ConclusionInteractive discussions through audiovisual media and peer education modules enhance adolescents’ cognitive ability to solve unwanted pregnancy problems, and are significantly influenced by family factors.